Prazer, sofrimento e estratégias de mediação no trabalho em saúde : um estudo de caso - Pedro, Marcia João (Universidade Federal de São Carlos, 2015)
The present study has how aim to identify the existence of pleasure and suffering and respective strategies of mediation among the health´s area professionals. The place is a Public University located in the state of São Paulo state, in its medium complexity specialties ´s outpatient department, which is characterized for joining the work of teaching assistance, researching and extension. It´s an exploratory descriptive qualitative study, which took as methodology the use of the ITRA - (RIWI) (Risk Illness Work´s Inventory), to collect objective data and semi-structured interview for more subjective data collection, investigating the impressions of individuals about experiences at work. Participated in the survey 19 out of the 26 personnel in the local office. For the interview data analysis has been used the Baldin´s Analisysis Content and to the results interpretation the chosen theory was the Work´s Psychodynamic. Nowadays is identified in some health sectors a frequent suffering, which does those health professionals to suffer, leading to identify this project as important relevance. The reached result with this study surprises regarding the peculiar field aspects that is shown with an idealized prescribed work proposal the on the daily reality is not fulfilled as idealized leading to suffering face this contrariness. Among the aspects that indicates suffering are public services management problems that is bureaucratic hindering the workflow and difficulties to establishing the relations interdisciplinary/intersensory for the work achievement in such a way that it answers to the prescribed models. However, by having a shared management it gives opportunity to people through the sharing and acting freedom in your areas finding creative solutions for the suffering experienced in life, presenting defensives mediation strategy and subjective mobilization, this last is considered the healthier way to face the work suffering, according with work´s psychodynamic. This within others aspects reveals an environment with many pleasurable experiences that are balanced by the suffering existences, highlighting the feelings of professional realization, recognition gratification and valorization.
Keywords: Saúde e trabalho; Psicodinâmica do trabalho; Estratégias de Mediação; Prazer; Sofrimento; Health professional; Worker health. work´s psychodynamic; Pleasure; Suffering; Mediation strategies; CIENCIAS DA SAUDE